Basic measurement concepts. Issue 4 (April 2023) - Wild, Christopher; Zin, Nico
Abstract: Accurate monitoring and measurement of physiological parameters is fundamental in modern anaesthetic practice. The physical parameter being measured is known as the measurand. A measurement system can be thought of as a 'black box' whereby an input is processed, yielding an output. Components of a system include a sensor, transducer, signal conditioning unit, and display. A solid understanding of these devices and their strengths, limitations and sources of error is fundamental in the delivery of safe and appropriate care. Signal conditioning involves reducing background noise, amplification and filtering of the signal, and analogue-to-digital conversion. The output of the measurement system should accurately reflect the parameter being measured. Performance of a measurement system can be characterised by its static and dynamic characteristics, including accuracy, precision, sensitivity and linearity. Clinical measurement systems behave like first-order or second-order dynamic systems. They are subject to drift and hysteresis, necessitating regular calibration. Error may be inherent to the equipment itself or user misinterpretation. This article outlines the basic principles of these measurement devices.